Comparison of pyruvate kinase variants from breast tumor and normal breast - Yilmaz, S; Ozan, S; Ozercan, IH (Elsevier Science Inc, 2003)
Background. Pyruvate kinase isozymes in human breast tumor tissue were compared in this study with normal human breast tissue. Two forms of pyruvate kinase present in normal and tumor human breast were purified by ammonium sulfate precipitation, dialysis, gel filtration, ion exchange, and affinity chromatography. Molecular weight of the native enzyme was determined. Methods. Presence of pyruvate kinase activity was examined in normal and tumor breast tissues. Pyruvate kinase was purified with Sephadex DEAE-50, Sepharyl S-200, and Blue Sepharose CL-6B chromatography. Spectrophotometric methods were used to determine activities of pyruvate kinase. Results. Molecular weights of fractions I and II as determined by gel filtration on Sepharyl S-200 were 135,000 Da, 260,000 Da in normal breast tissue, and 72,000 Da, 250,000 Da in tumor breast tissue, respectively. Fractions I and II of pyruvate kinase may be purified approximately 1,591-fold, 636.4-fold in normal breast tissue and 219-fold, 318-fold in tumor breast tissue, respectively. Pyruvate kinase activity in tumor tissue was found higher than in normal tissue. Only tumor fraction II showed tumor-specific sensitivity to L-cysteine. L-phenylalanine inhibited both fractions I and II of normal breast and fraction I of tumor breast, but not fraction II of pyruvate from tumor. ATP inhibited normal and tumor fraction I of pyruvate kinase. The influence of ATP on enzyme activity from normal and tumor fraction II depended upon its concentration. Conclusions. It was thought that isozymes of pyruvate kinase from human breast tissue might be M-1 and M-2 isozymes when compared with those of other tissue pyruvate kinase isoenzymes. Fraction II from breast tumor represented different sensitivity to L-cysteine, L-phenylalanine, and specific activity in comparison with fraction 11 from normal breast. Different kinetic behavior of fractions in the human breast tumors may support the concept of an isozyme shift. (C) 2003 IMSS. Published by Elsevier Science Inc.
Keywords: human breast; tumor; pyruvate kinase; purification; molecular weight